2014
DOI: 10.1590/0004-282x20140037
|View full text |Cite
|
Sign up to set email alerts
|

Limb-girdle muscular dystrophy in Brazilian children: clinical, histological and molecular characterization

Abstract: Limb-girdle muscular dystrophies (LGMD) are a heterogeneous group of genetic muscular dystrophies, involving 16 autosomal recessive subtypes and eight autosomal dominant subtypes. Autosomal recessive dystrophy is far more common than autosomal dominant dystrophy, particularly in children. The clinical course in this group is characterized by progressive proximal weakness, initially in pelvic and after in shoulder-girdle musculature, varying from very mild to severe degree. Significant overlap of clinical pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
2
0
2
Order By: Relevance
“…Our epidemiological profile is similar to recent large samples studies from Italy and the United States; however, it partially differed from previous Brazilian reports more focused on the pediatric population. A previous single‐center study in São Paulo reported that sarcoglycanopathies were diagnosed in 40.5% of a series of 37 children with LGMD2/LGMD‐R . A single‐center study from southern Brazil evaluated 56 patients with LGMD only with immunohistochemistry and reported sarcoglycanopathies (32%) as the most common diagnosis, followed by LGMD2B/LGMD‐R2‐dysferlin‐related (14.3%) and LGMD2A/LGMD‐R1‐calpain3‐related (8.9%) .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our epidemiological profile is similar to recent large samples studies from Italy and the United States; however, it partially differed from previous Brazilian reports more focused on the pediatric population. A previous single‐center study in São Paulo reported that sarcoglycanopathies were diagnosed in 40.5% of a series of 37 children with LGMD2/LGMD‐R . A single‐center study from southern Brazil evaluated 56 patients with LGMD only with immunohistochemistry and reported sarcoglycanopathies (32%) as the most common diagnosis, followed by LGMD2B/LGMD‐R2‐dysferlin‐related (14.3%) and LGMD2A/LGMD‐R1‐calpain3‐related (8.9%) .…”
Section: Discussionsupporting
confidence: 82%
“…LGMD2/LGMD‐R are the most common group of these disorders, but relative frequencies among LGMD2/LGMD‐R subtypes vary from region to region . There is a lack of epidemiological data about LGMD in Latin America, with only few single‐center studies reporting sarcoglycanopathies as the most frequent subtypes in Brazil …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Також поступово виникли труднощі з утриманням важких предметів в руках та рук над головою (рис. [1][2][3].…”
Section: випадокunclassified
“…Ключові слова: кінцівково-поясна м'язова дистрофія; ген CAPN3; прийом Говерса; проксимальна м'язова слабкість Вступ Кінцівково-поясна м'язова дистрофія (LGMD)це неоднорідна група генетично обумовлених нервовом'язових захворювань, що характеризуються прогресуючою слабкістю і атрофіями м'язів тазового та плечового поясів, а також значно варіабельним перебігом захворювання [1]. Найчастіше при даних формах м'язових дистрофій уражуються м'язи плечей, верхніх кінцівок, тазового пояса та стегон [2,3].…”
unclassified